Orbital Phase-resolved Analysis of X-Ray and Gamma-Ray Observations of the High-mass Gamma-Ray Binary 4FGL J1405.1−6119 - Alexander Lange; Robin H.D. Corbet; Joel B. Coley; Guillaume Dubus; Jeremy Hare; Nazma Islam; Jonathan Barnes (The Astrophysical Journal)
We present the results of multiwavelength observations of the high-mass gamma-ray binary (HMGB) 4FGL J1405.1−6119. A pair of joint XMM-Newton and NuSTAR observations taken in 2019 (sampling the gamma-ray maximum and X-ray maximum) characterize the emissiong of soft and hard X-rays. We find variability of the hydrogen column density along our line of sight, N _H , and photon index, Γ, and find no evidence of pulsations in X-rays. We also refine a new best-fit orbital period to P  = 13.7157 ± 0.0014 days, the first orbital phase-resolved analysis based on nearly 16 yr of Fermi-LAT observations of 4FGL J1405.1−6119 and the evolution of the spectral shape as a function of orbital phase. Finally, the X-ray and gamma-ray spectra for the phases sampled in the new X-ray observations can be interpreted in the framework of the intrabinary shock model, previously applied to HMGBs such as LS 5039.